Growth and Fabrication of Quasivertical Current Aperture Vertical Electron Transistor Structures. Issue 3 (23rd September 2020) - Doering, Philipp; Driad, Rachid; Leone, Stefano; Mueller, Stefan; Waltereit, Patrick; Kirste, Lutz; Polyakov, Vladimir; Mikulla, Michael; Ambacher, Oliver
Abstract : The current aperture vertical electron transistor (CAVET) combines the high carrier mobility of the AlGaN/GaN heterostructure with the better electric field distribution of the vertical topology, allowing for higher power densities if compared with lateral high electron mobility transistors (HEMTs). The formation of a current blocking layer (CBL), without degenerating the aperture region and the subsequently overgrown AlGaN/GaN heterostructure is the key building block of such devices. Herein, a comparison of GaN:Mg nonplanar selective area growth (SAG) and Mg‐ion implantation is carried out primarily focusing on structural evolution, Mg distribution, and 2D electron gas (2DEG) performance. The epitaxial growth process in SAG is correlated to local growth increase and ridge development, and then optimized regarding mesa filling. AlGaN/GaN regrowth is analyzed regarding structural evolution after overgrowth and Mg distribution into the GaN channel. Considerably lower Mg‐distribution into subsequently grown layers is detected for implanted samples in agreement with the electrical performance of the overgrown AlGaN/GaN heterostructures. A GaN‐on‐Si quasivertical CAVET structure with an Mg‐implanted CBL and 250 nm channel thickness is fabricated. High surface quality and proper 2DEG performance demonstrate the potential use of GaN‐on‐Si CAVET's using Mg implantation for CBL fabrication. Abstract : The formation of a current blocking layer is the key building block of the current aperture vertical electron transistor. Herein, a comparison of GaN:Mg nonplanar selective area growth and Mg‐ion implantation is carried out primarily focusing on structural evolution, Mg distribution, and 2D electron gas performance.